Manajemen Pengembangan Daerah Aliran Sungai (DAS) Sebagai Daya Tarik Pariwisata Bekelanjutan Studi Kasus Daerah Aliran Sungai Ayung. - Eka Putra, Widhi Adnyana (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe Utilization of watersheds in Bali indirectly provides benefits and impacts; both positive and negative impacts for watershed sustainability. In order to minimize the impact, sustainable tourism development efforts are made to maintain and improve socio-cultural, socio-economic, and ecological. This research was taken in order to optimalize the using of watershed as sustainable tourism attraction. Therefore, the concept of sustainable development and tourism is used to develop watershed management as a sustainable tourism attraction. Ayung watershed was used as the object of the research based on masive exploitation along the watershed. There were several Instruments which was used in this study, such as interview guidelines for in-depth interviews, questionnaire (a questionnaire containing internal and external factors) and tools such as cameras, and notes for observation, which are then processed by descriptive-qualitative analysis techniques. Based on the results of research that has been implemented, there are 5 (five) strategies that can be used to improve watershed management, such as: 1). Sustainable Forest Management Strategy; 2). Law Enforcement Strategy; 3). Community Empowerment Strategies; 4). Integrated Management Strategy; and 5) .Economic Improvement Strategy. Keywords: Development, Sustainable Tourism, Watershed